2001
DOI: 10.4065/76.5.503
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in reduction mammaplasty: a systematic review and meta-analysis of published studies

Abstract: This systematic review and meta-analysis were undertaken to determine whether reduction mammaplasty improves measurable outcomes in women with breast hypertrophy. A systematic review of the literature in 5 languages from 1985 until March 1999 was performed, and data were compared for meta-analysis. Eligible studies were both experimental and observational and involved women with preoperative physical and/or psychosocial signs and symptoms who underwent reduction mammaplasty for breast hypertrophy. Outcomes ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 46 publications
(99 reference statements)
6
68
0
17
Order By: Relevance
“…Similar prospective studies were conducted by Blomqvist et al (11) and Behmand et al (12), but with short-term postoperative follow-up periods ranging from six to 12 months. Behmand et al's analysis of the study performed by Chadbourne et al (13) reported that reduction mammoplasty improved the physical and psychological symptoms associated with breast hypertrophy. Thoma et al (14) demonstrated that breast reduction results in the improvement of breast hypertrophy symptoms within a month following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similar prospective studies were conducted by Blomqvist et al (11) and Behmand et al (12), but with short-term postoperative follow-up periods ranging from six to 12 months. Behmand et al's analysis of the study performed by Chadbourne et al (13) reported that reduction mammoplasty improved the physical and psychological symptoms associated with breast hypertrophy. Thoma et al (14) demonstrated that breast reduction results in the improvement of breast hypertrophy symptoms within a month following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…shown to be inconsistent for comparisons (4,13,14) . The evaluation of spinal pain and restraints resulting from these symptoms in patients with breast hypertrophy, assessed from a patient's point of view, and using instruments of which measurement properties have already been tested, lends higher reliability to the study.…”
Section: Table 2 -Comparisons Of Groups Regarding Variables Of Pain Amentioning
confidence: 99%
“…Sintomas que vão desde síndrome do túnel do carpo até dor na coluna e diminuição da capacidade funcional apresentam melhora com a mamoplastia redutora (20,21) .…”
Section: Pacientes E Métodosunclassified